STRATEGI GURU PAUD DALAM MENDUKUNG KEMAMPUAN BERBICARA ANAK DENGAN HAMBATAN SPEECH DELAY (STUDI KASUS ANAK KELAS A USIA 7 TAHUN DI TKIT AL-MUHAJIRIN KOTA CILEGON) - Dian Nurrizka Dewi; Dina Kusuma Wardhani; Tri Sayekti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Speaking ability is one of the essential aspects of early childhood language development that influences children's social, emotional, and cognitive growth. However, not all children develop speaking skills according to their developmental stage. One of the common problems found in early childhood is speech delay. This study aimed to describe teachers' strategies in supporting the speaking ability of children with speech delay, the interaction approaches and language stimulation provided by teachers, as well as the supporting and inhibiting factors encountered in their implementation. This research employed a qualitative approach with a case study design. The research subject was a seven-year-old child with speech delay in Class A of TKIT Al-Muhajirin, Cilegon City. The research informants consisted of the classroom teacher and the principal. Data were collected through observation, interviews, and documentation. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings revealed that the strategies implemented by teachers included individualized approaches, gradual learning activities adjusted to the child's abilities, intensive guidance and direction, the use of learning media, and the creation of a safe and supportive classroom environment that encourages communication. Supporting factors included the principal's support, adequate learning media, collaboration with parents, and coordination with psychologists. Meanwhile, the obstacles encountered included limited special services because the school is not an inclusive school and the child's difficulties in participating in certain learning activities. The gradual and consistent implementation of these strategies showed a positive impact on the development of the child's speaking ability and social interaction. Keywords: teacher strategies, speech delay, speaking ability, early childhood.